2019
DOI: 10.1016/j.oceaneng.2018.12.052
|View full text |Cite
|
Sign up to set email alerts
|

On hydrodynamic characteristics of gap resonance between two fixed bodies in close proximity

Abstract: The resonant water motion inside a narrow gap between two identical fixed boxes that are in side-by-side configuration is investigated using a two-dimensional (2D) numerical wave tank based on OpenFOAM ® , an open source CFD package. Gap resonance is excited by regular waves with various wave heights, ranging from linear waves to strong nonlinear waves. This paper mainly focuses on the harmonic analyses of the free-surface elevation in the narrow gap and wave loads (including the horizontal wave forces, the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…Jiang et al [23] and Gao et al [26] found that the wave response in the gap decreased with the increasing of wave height, while the resonant frequency in the gap were nearly the same. When the wave resonances in the gap near ω=2.79 rad/s, the dissipation coefficient increases and the conversion efficiency decreases suddenly for the hybrid system with the triangular WEC, as shown in Fig.…”
Section: Effect Of Incident Wave Height Hi/hmentioning
confidence: 98%
See 1 more Smart Citation
“…Jiang et al [23] and Gao et al [26] found that the wave response in the gap decreased with the increasing of wave height, while the resonant frequency in the gap were nearly the same. When the wave resonances in the gap near ω=2.79 rad/s, the dissipation coefficient increases and the conversion efficiency decreases suddenly for the hybrid system with the triangular WEC, as shown in Fig.…”
Section: Effect Of Incident Wave Height Hi/hmentioning
confidence: 98%
“…The results revealed that large amount of vortices were generated by the sharp corners of the two barges and shed downward, and the viscous damping associated with the twin-barge system was demonstrated dependent on the incident wave steepness. Gao et al [26] used OpenFOAM software to investigate the resonant water motion inside a narrow gap between two identical fixed boxes those were in the side-by-side configuration, and the free-surface elevation in the narrow gap, wave loads on the bodies and the effects of the incident wave height on the reflection, transmission and energy loss coefficients were analyzed. It is not possible to infer the effect of wave resonance in the WEC-breakwater gap on the energy extraction performance of the dual-floater system from existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…79 In other words, under the action of wave breaking, bow wave and jet, bubbles were formed in water. 10–12 Studies showed that the bow wave drew air into the water, which caused the formation of bubbles. Bubbles flowed backward along the ship bottom.…”
Section: Introductionmentioning
confidence: 99%
“…Most objects of the research studies on the shear layer oscillation were aerodynamic cavity instead of the moonpool [19][20][21][22][23]. e shear oscillation was studied by visual methods such as laser Doppler velocity measurement (LDA) and particle image velocimetry (PIV) [24][25][26].…”
Section: Introductionmentioning
confidence: 99%